ZIKR QUALITY RELATIONSHIP WITH HAPPINESS AT AKTIVIS DAKWAH KAMPUS (ADK) STUDENT UNSYIAH - Jasmadi - Ali; lailatul - muslimah (Psikoislamedia : Jurnal Psikologi, 2016)
Aktivis Dakwah Kampus (ADK) is known as a religious students. They are struggling in various areas of the organization that led to the ADK has many responsibilities and routines are full every day. Density of activity can get ADK exhausted and futur which resulted in the onset of stress, depression and anxiety causing ADK’s unhappiness. Therefore, ADK requires the strength that comes from daily devotions, one of wich is the zikr. The purpose of this research is to understand about relationship between zikr quality and happiness of ADK Universitas Syiah Kuala (Unsyiah). The population of this research is entire ADK Unsyiah. Sampling technique used in this research is non probability sampling specifically purposive sampling. Selected sample according to Slovin’s formula is 100 subjects. The method of data collecting used scale of zikr quality consisting of 30 items and scale of happiness consisting of 17 items. Data analisis used Pearson’s correlation technique of parametric statistic by correlation coefficient = 0.326 and p = 0.001 (p < 0.01). The result revealed significantly positive correlation between zikr quality and happiness of ADK Unsyiah meant the higher zikr quality reached. The higher ADK’s happiness can get. As well as, lower zikr quality reached the lower ADK’s happiness.